KINETICS STUDY OF THE DISPROPORTIONATION OF THE IODOUS ACID IN AQUEOUS SULFURIC ACID SOLUTION - Marković, Smiljana; Petrović, Biljana (Bulletin of Natural Sciences Research, 2016)
In this paper we reported the kinetics of the disproportionation reaction of iodous acid (HOIO) in aqueous sulfuric acid solutions (0.18 mol/dm3) studied by spectrophotometrical measurements of the absorbance at suitable wavelength. The changes of the absorbance were caused because the absorbing I2 molecule species were generated during the reaction. The disproportionation rate constants are calculated at the temperature range between 285 and 303 K with average values: k285 = (0.90 ± 0.08) dm3mol-1s-1, k291 = (1.10 ± 0.10) dm3mol-1s-1, k298 = (1.30 ± 0.07) dm3mol-1s-1and k303 = (1.50 ± 0.10) dm3mol-1s-1, respectively. The corresponding activation energy was determined, for the chosen temperature interval, by a graphical method. In addition, obtained value of activation energy is Ea = 38 ± 5 kJ/mol. The negative value of Gibbs energy change and other thermodinamical parameters show that is the disproportionation reaction thermodynamically feasible.   Keywordsiodous acid;disproportionation reaction;rate constants;activation energy.